Paediatric cholestatic liver disorders for the adult gastroenterologist: a practical guide. Issue 5 (3rd August 2020) - Kelly, Claire; Nayagam, Jeremy Shanika; Vogli, Stamatina; Samyn, Marianne; Joshi, Deepak
Abstract : With improvements in the outcomes for cholestatic liver diseases that present in childhood, increasing numbers of patients will require ongoing care as adults. The recent advances in management options coupled with the fact that each adult physician will have a limited number of patients with these conditions means there is a need for those in adult services to develop expertise in these conditions that were historically the domain of paediatrics. This review provides an overview of the most common paediatric cholestatic liver diseases and outlines the clinical manifestations and potential complications, and identifies key management issues unique to each condition for effective ongoing care of these patients.